Assessing the impact of TRAP laws on abortion and women's health in the USA: a systematic review. Issue 2 (9th March 2018) - Austin, Nichole; Harper, Sam
Abstract : Introduction: Targeted Regulation of Abortion Providers (TRAP) laws impose extensive and sometimes costly requirements on abortion providers and facilities, potentially leading to barriers to care. Understanding the impact of these laws is important given their prevalence in the USA, but no review to date has summarised the available evidence. We conducted a systematic review of literature on TRAP laws and their impact on abortion trends and women's health. Methods: We searched MEDLINE, PubMed and EconLit for original, quantitative studies where the exposure was at least one TRAP policy and the outcome was abortion and/or any women's physical or mental health outcome. Results: Six articles met our inclusion criteria. The most common outcome was population-level abortion trends; studies also assessed the effect of TRAP laws on gestational age at presentation and measures of self-perceived burden. While certain TRAP laws (eg, admitting privilege requirements) appeared to have an effect on abortion outcomes, the impact of other laws – or combinations of laws – was unclear, due in part to heterogeneity between studies with respect to study design, geography, and exposure definition. Conclusions: TRAP laws may have an impact on the experience of obtaining an abortion in the USA. However, our review revealed a paucity of empirical research on their population and individual-level impact, as well as some disagreement about the effect of different TRAP laws on subsequent abortion outcomes. Future research should prioritise the specific TRAP laws that may have a uniquely strong effect on state-level abortion rates and other outcomes.